Delivering siRNA Compounds During HOPE to Modulate Organ Function: A Proof-of-concept Study in a Rat Liver Transplant Model. Issue 8 (18th May 2022) - Bonaccorsi-Riani, Eliano; Gillooly, Andrew R.; Iesari, Samuele; Brüggenwirth, Isabel M.A.; Ferguson, Chantal M.; Komuta, Mina; Xhema, Daela; Daumerie, Aurélie; Maistriaux, Louis; Leuvenink, Henri; Kupiec-Weglinski, Jerzy; Porte, Robert J.; et al.
Abstract : Background: Apoptosis contributes to the severity of ischemia-reperfusion injury (IRI), limiting the use of extended criteria donors in liver transplantation (LT). Machine perfusion has been proposed as a platform to administer specific therapies to improve graft function. Alternatively, the inhibition of genes associated with apoptosis during machine perfusion could alleviate IRI post-LT. The aim of the study was to investigate whether inhibition of an apoptosis-associated gene (FAS) using a small interfering RNA (siRNA) approach could alleviate IRI in a rat LT model. Methods: In 2 different experimental protocols, FASsiRNA (500 µg) was administered to rat donors 2 h before organ procurement, followed by 22 h of static cold storage, (SCS) or was added to the perfusate during 1 h of ex situ hypothermic oxygenated perfusion (HOPE) to livers previously preserved for 4 h in SCS. Results: Transaminase levels were significantly lower in the SCS-FASsiRNA group at 24 h post-LT. Proinflammatory cytokines (interleukin-2, C-X-C motif chemokine 10, tumor necrosis factor alpha, and interferon gamma) were significantly decreased in the SCS-FASsiRNA group, whereas the interleukin-10 anti-inflammatory cytokine was significantly increased in the HOPE-FASsiRNA group. Liver absorption of FASsiRNA after HOPE session was demonstrated by confocal microscopy; however, no statistically significant differences on the apoptotic index, necrosis levels, and FAS protein transcription between treated and untreated groups were observed. Conclusions: FAS inhibition through siRNA therapy decreases the severity of IRI after LT in a SCS protocol; however the association of siRNA therapy with a HOPE perfusion model is very challenging. Future studies using better designed siRNA compounds and appropriate doses are required to prove the siRNA therapy effectiveness during liver HOPE liver perfusion. Abstract :